(untitled) (American Journal of Smart Technology and Solutions, 2025)
The rise in integration of Artificial Intelligence (AI) tools in different sectors has generated a substantial impact in their prospective applications in the academic sector. This study analyzes the interest in adopting AI technologies in post-secondary education, mainly focusing on developing countries. It assesses the benefits, complications, and ethical considerations linked with the usage of AI in academic practices, including teaching, training, learning, and research. By conducting a thorough review of existing literature, the work highlights key benefits of AI adoption, for instance enhanced educational experiences, possibilities for personalized learning, and optimized administrative efficiency. Moreover, the study responds to potential challenges, such as biases in AI systems, threats to social engagement and critical thinking, and the negative impact on creativity within academic environments. To efficiently leverage AI’s advantages while maintaining fundamental educational values, the study proposes strategic ways for successful AI integration. Also, the paper underscores the significance of considering the distinctive context of developing nations, especially the issues related to limited resources and the necessity to make assure equal availability to AI technologies. By addressing these challenges, the study aims to give a roadmap for effectively and responsibly adopting AI technologies into higher education systems.